The Evolution of Urban Policy in Seville (Spain): Scope and Limits for the Promotion of Socioeconomic and Territorial Inclusion - Tadeu Terci, Eliana (Revista del CLAD Reforma y Democracia, 2022)
This article analyzes the evolution of urban policy in the city of Seville (Spain) in a context marked by the advance of neoliberalism, productive restructuring, deregulation of the market and of the city’s protagonism. The aim is to evaluate the scope and limits of urban policy to reverse the indicators of socioeconomic and territorial exclusion and to reduce inequality. It results from exploratory research using two bases: the interdisciplinary bibliography that focuses on the urban phenomenon under multiple approaches and the institutional sources that systematize socioeconomic, demographic and statistical data and that allow evaluating the recent evolution of Seville. The results show that the focus of urban policy on the construction and qualification of high-quality business spaces, characteristic of urban entrepreneurship, in the face of excessive deregulation of the labor market, low levels of income per capita and per household, accentuates the duality of the labor market and hinders the challenges of socio-territorial inclusion.
Keywords: Urban Policy; Urban Reform; Urban Area; Case Analysis; Spain